2008
DOI: 10.1519/jsc.0b013e31817ae4a7
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Elastic Energy in Activities with High Force and Power Requirements: A Brief Review

Abstract: The purpose of this article is to provide strength and conditioning practitioners with an understanding of the role of elastic energy in activities with high force and power requirements. Specifically, the article covers 1) the nature of elasticity and its application to human participants, 2) the role of elastic energy in activities requiring a stretch-shorten cycle such as the vertical jump, 3) the role of muscular stiffness in athletic performance, 4) the control of muscular stiffness through feedforward an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(80 citation statements)
references
References 37 publications
3
70
0
7
Order By: Relevance
“…This might offer one approach to identify those at increased risk of injury; players who have substantially reduced leg stiffness and a disproportionate decrease in background muscleactivity may be at increased injury risk with fatigue. This is because reduced preactivation may cause greater yielding (Wilson and Flanagan 2008), decrease stability (Padua et al 2005) and increase stress on ligaments (Hewett et al 2005). The present findings may help to begin to explain the high incidence of ankle and knee injuries during match-play, with incidence known to increase towards the end of the first half of a match (Ekstrand et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might offer one approach to identify those at increased risk of injury; players who have substantially reduced leg stiffness and a disproportionate decrease in background muscleactivity may be at increased injury risk with fatigue. This is because reduced preactivation may cause greater yielding (Wilson and Flanagan 2008), decrease stability (Padua et al 2005) and increase stress on ligaments (Hewett et al 2005). The present findings may help to begin to explain the high incidence of ankle and knee injuries during match-play, with incidence known to increase towards the end of the first half of a match (Ekstrand et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Leg stiffness describes the multi-joint response of the lower limbs to generate force and resist deformation during rebounding activities (Komi 2000;Padua et al 2005). Increased leg stiffness is suggested to enhance rate of force development, locomotor kinematics and energy storage and utilisation (Brughelli and Cronin 2008), providing performance benefits of increased force output, movement speed and running economy (Butler et al 2003;Wilson and Flanagan 2008). Furthermore, it has been suggested that lower limb stiffness is an important injury protection mechanism (Alentorn-Geli et al 2009), with low levels of stiffness associated with soft tissue injuries (Hobara et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of the fast SSC could be improved by increasing leg stiffness, which is achieved by decreasing range of knee flexion, therefore improving jumping ability (30). Thus, the control group produced a more effective SSC.…”
Section: Drop Jumpmentioning
confidence: 99%
“…A divergência entre os resultados deste e de outros estudos, no que se refere à variabilidade da relação entre diferentes tipos de saltos com a agilidade e velocidade demonstra a complexidade em predizer este tipo de desempenho, o qual é determinado por diferentes fatores. Os fatores associados ao desempenho da agilidade e velocidade são a transferência rápida de energia 28 , predominância de fibra muscular de contração rápida, aumento da excitabilidade do motoneurônio e velocidade de condução nervosa 29 , desenvolvimento de força concêntrica 30 , potência e torque muscular 31 , utilização do ciclo alongamento encurtamento 32 , tempo de contato com o solo 33 e condição de treinamento 34 . Dentre os fatores determinantes do desempenho, um dos aspectos que é comum ao desempenho do salto, da velocidade e da agilidade é a utilização da energia elástica, produzida pelo ciclo de alongamento e encurtamento para produzir força 32 .…”
Section: Descrição Dos Testesunclassified